Immediate Effect of Customized Foot Orthosis on Plantar Pressure and Contact Area in Patients with Symptomatic Hallux Valgus - Hsin-Yu Chen; Hsien-Te Peng; Chin-Kang Chang; Fu-Ting Wang; Chia-Hao Yen; Tsung-Yang Wang; Hsiang-Chun Chuang; Fang-Yao Chiu; Chen-Yi Song (Applied Sciences, 2022)
Foot orthotics are recommended for the treatment of hallux valgus. The effects of customized foot orthoses (FOs) designed with both medial longitudinal and transverse arch supports are poorly understood, however. This study aimed to investigate the immediate effect of customized FOs on the plantar pressure and contact area in patients with symptomatic hallux valgus. We recruited 18 patients with a mean hallux valgus angle of 27.3 ± 11.1°. Plantar pressure while walking with FOs or flat insoles (FIs) was monitored with a wireless in-shoe plantar pressure-sensing system. Peak pressure (PP), peak force (PF), pressure-time integral (PTI), force-time integral (FTI), and contact area with FOs and FIs were compared. The PF, PTI, and FTI of the midfoot were significantly higher (p < 0.05), and the PP and PTI of the rearfoot were significantly lower (p < 0.05) with the FOs than the FIs. The FOs significantly increased the contact area of the midfoot and rearfoot (p < 0.05) and reduced the contact area of the forefoot (p < 0.05). These results suggest that customized FOs redistribute plantar pressure and the contact area of the midfoot and rearfoot, improving the functional support of the midfoot for patients with hallux valgus.